1997
DOI: 10.1007/s002340050358
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal neurocysticercosis: follow-up and staging by MRI

Abstract: We describe the evolution of parenchymal cerebral cysticerci on MRI, to assess signs of early cyst degeneration. We studied 15 lesions in four treated and one untreated patient. MRI was performed before therapy and repeated in the 1st month after each course of anticysticercus drugs, every 4 months during the 1st year and then annually; the follow-up period was 8-48 months. Lesions were classified according to changes in four features: cyst content and capsule signal, gadolinium enhancement and oedema signal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 18 publications
1
56
0
5
Order By: Relevance
“…Neuroimaging studies [15][16][17] constitute a rather effective tool in patients suspected to have NC. Byrd et al 15 described the head CT findings in 30 adults and 15 children (age range, 6-17 years) with NC, who were classified in four groups according to cyst location: parenchymatous (11 children), ventricular-cisternal (1 child), ependymal-meningeal (1 child), and mixed (2 children).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies [15][16][17] constitute a rather effective tool in patients suspected to have NC. Byrd et al 15 described the head CT findings in 30 adults and 15 children (age range, 6-17 years) with NC, who were classified in four groups according to cyst location: parenchymatous (11 children), ventricular-cisternal (1 child), ependymal-meningeal (1 child), and mixed (2 children).…”
Section: Discussionmentioning
confidence: 99%
“…Dumas et al 16 reported on the radiological progression of 15 NC lesions that were followed with serial MRI studies, and were able to define five stages of neuroradiologic evolution, according to cysticercus content signal-intensity compared with CSF, presence and degree of surrounding edema, and contrast enhancement. Lesions in stage 1 resolved without progression to subsequent stages in response to specific treatment, while stage 4 lesions involuted even without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent consensus proposing diagnostic criteria for NC, several images were emphasized and classified as absolute, major and minor criteria 19 . Neuroimaging is strongly applied in the diagnosis for NC, permitting visualization of the parasite in its different stages [20][21][22] . Examination of cerebrospinal fluid (CSF) may be a valuable diagnostic tool, providing sensitive information about the inflammatory process and activity of NC [23][24][25][26][27] .…”
Section: Resumo -Objetivomentioning
confidence: 99%
“…At this stage the inflammation and edema associated with the degenerating lesion are markedly decreased. 4,5 With time, the involuted lesion undergoes complete calcification or resorption. At this stage, the infection is no longer considered to be active.…”
Section: Case Reportmentioning
confidence: 99%